Assessing edge effect on the spatial distribution of selected forest biochemical properties derived using the Worldview data in Dukuduku forests, South Africa. (25th March 2019) - Mutanga, Onisimo; Dube, Timothy; Omer, Galal
Abstract: This work explores the potential of the high‐resolution WorldView‐2 sensor in quantifying edge effects on the spatial distribution of selected forest biochemical properties in fragmented Dukuduku forest in KwaZulu‐Natal, South Africa. Specifically, we sought to map fragmented patches within forested areas in Dukuduku area, using very high spatial resolution WorldView‐2 remotely sensed data and to statistically determine the effect of these fragmented patches on the spatial distribution of selected forest biochemical properties. Edge effects on carbon, LAI and foliar nitrogen were quantified based on the models derived by Omer et al. ( IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing, 2015, 8, 4825). Edge effect statistical results on the spatial distribution of carbon, LAI and nitrogen showed significant ( α = 0.05) variations with change in distance from fragmented patches (>150 m 2 ). Forest foliar carbon concentrations significantly ( p ‐value = 0.016) increased from 44.8% to 45.3% with increasing distance (25–375 m) from fragmented patches. A similar trend was observed for LAI. Nevertheless, for nitrogen the results show that its concentration significantly ( p = 0.016) decreased with increase in distance from the fragmented patches. Overall, the findings of this work underscore the invaluable potential and strength of WorldView‐2 data set in assessing edge effect on the spatial distribution of selected forest biochemical properties. Résumé: Ce travail étudie le potentiel du capteur de haute résolution WorldView‐2 dans la quantification des effets de bord sur la distribution spatiale des propriétés biochimiques de forêt sélectionnées dans la forêt fragmentée de Dukuduku du KwaZulu‐Natal, en Afrique du Sud. Plus précisément, nous avons cherché à cartographier des parcelles fragmentées au sein des surfaces forestières dans la région de Dukuduku, en utilisant des données de télédétection WorldView‐2 à très haute résolution spaciale et à déterminer statistiquement l'effet de ces parcelles fragmentées sur la distribution spatiale des propriétés biochimiques forestières sélectionnées. Les effets de bord sur le carbone, le LAI et l'azote foliaire ont été quantifiés sur la base des modèles dérivés par Omer et al. (2015). Les résultats statistiques d'effet de bord sur la distribution spatiale du carbone, du LAI et de l'azote ont montré des variations significatives (α = 0, 05) avec le changement de distance par rapport à des parcelles fragmentées (> 150 m2). Les concentrations de carbone foliaires des forêts ont augmentées de manière significative (valeur p = 0, 016) de 44, 8 à 45, 3% avec l'augmentation de la distance (25 m à 375 m) des parcelles fragmentées. Une tendance similaire a été observée pour le LAI. Néanmoins, pour l'azote, les résultats montrent que sa concentration (p = 0, 016) a diminué avec l'augmentation des parcelles fragmentées. Globalement, les résultats de ce travail soulignent le potentiel et la force inestimables de l'ensemble des données du WorldView‐2 dans l'évaluation de l'effet de bordure sur la distribution spatiale de propriétés biochimiques des forêts sélectionnées.